Sleep-disordered Breathing in Japan: An Overview - Kawakami, Y; Hishikawa, Y; Takishima, T; Katayama, S; Okada, T; Kuriyama, T; Kuno, K; Ohta, Y; Suetsugu, S; Togawa, K (Nihon Kyōbu Shikkan Gakkai zasshi, 1993)
Questionnaires were answered by 3, 243 presumably healthy subjects who underwent regular medical checkups in four cities. The prevalences of risk factors for sleep-disordered breathing (SDB) were as follows; habitual snoring was reported by 13-16%, excessive daytime sleepiness by 8-9%, insomnia by 7-13% and systemic hypertension by 5-13%. Polysomnographic studies performed on some possible SDB cases who were selected by the presence of risk factors estimated that the average prevalence of SDB in the present population would be in the range of 1.14-1.94%. Secondly, questionnaires were sent to the main hospitals and institutes involved in the management of patients with SDB, asking about diagnostic criteria, number of SDB patients, management, effectiveness of treatment, etc. The total number of patients registered at those hospitals was 2, 751 in 1991. Of the 132 patients who were followed for more than six months, the efficacies of body weight loss, medications, nasal CPAP and UPPP were compared. Based on the analyses of the 279 patients examined some tentative vriteria for diagnosis and for treatment are proposed.